2013
DOI: 10.1111/ele.12153
|View full text |Cite
|
Sign up to set email alerts
|

Increased competition does not lead to increased phylogenetic overdispersion in a native grassland

Abstract: That competition is stronger among closely related species and leads to phylogenetic overdispersion is a common assumption in community ecology. However, tests of this assumption are rare and field-based experiments lacking. We tested the relationship between competition, the degree of relatedness, and overdispersion among plants experimentally and using a field survey in a native grassland. Relatedness did not affect competition, nor was competition associated with phylogenetic overdispersion. Further, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 52 publications
7
82
1
Order By: Relevance
“…In return, fermentative TM7 may provide substrates to its filamentous host. Overall, our observation that co-occurring bacteria tend to be taxonomically less related essentially resembles the phylogenetic overdispersion of co-occurring species of plants or animals observed in many studies (Losos, 2008;Bennett et al, 2013), revealing that negative interactions (such as competition) have an important impact on the community assembly of large varieties of biological communities from microorganisms (for example, bacteria) to macroscopic plants and animals. Finally, the dominance of species-species correlations over those between environment and species, as well as the lack of strong correlations between environmental variables and many persistent OTUs, may relate to the fact that the activated sludge is kept operated/cultured in the artificially controlled (thus relatively stable) Shatin WWTP, where climates show no significant seasonal variations, thus, indicating that the variations in bacterial abundance were primarily driven more by biological interactions than by temporal changes in the physicochemical and operational parameters.…”
Section: Bacterial Assembly and Temporal Dynamics In As F Ju And T Zhangsupporting
confidence: 76%
“…In return, fermentative TM7 may provide substrates to its filamentous host. Overall, our observation that co-occurring bacteria tend to be taxonomically less related essentially resembles the phylogenetic overdispersion of co-occurring species of plants or animals observed in many studies (Losos, 2008;Bennett et al, 2013), revealing that negative interactions (such as competition) have an important impact on the community assembly of large varieties of biological communities from microorganisms (for example, bacteria) to macroscopic plants and animals. Finally, the dominance of species-species correlations over those between environment and species, as well as the lack of strong correlations between environmental variables and many persistent OTUs, may relate to the fact that the activated sludge is kept operated/cultured in the artificially controlled (thus relatively stable) Shatin WWTP, where climates show no significant seasonal variations, thus, indicating that the variations in bacterial abundance were primarily driven more by biological interactions than by temporal changes in the physicochemical and operational parameters.…”
Section: Bacterial Assembly and Temporal Dynamics In As F Ju And T Zhangsupporting
confidence: 76%
“…These assumptions have provided a useful foundation for our understanding of species interactions in a community context, yet our results show that the mechanisms of competition are not always evolutionarily conserved. Some studies have found evidence of phylogenetic overdispersion in natural communities [68][69][70][71][72][73], while others have not [18,20,21], suggesting that the pattern is not as widespread as predicted by the CRH. Contrary to those predictions, we show that close relatives of green algae do not compete strongly in bicultures and natural algal communities are not structured based on phylogenetic distance.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, invasive lineages of exotic species can differ in important reproductive and phenotypic traits (Meimberg et al 2010). However, most work to date has been based on the assumption that competitive effect or response is invariant within a species (Bennett et al 2013;Mariotte et al 2012) or that differences are between native and introduced populations of an invasive species Kumschick et al 2013). A better approach is to consider the role of intraspecific variation within the invaded range to account for potential trait differences resulting from dynamic relationships between introduction events and subsequent selection.…”
Section: Introductionmentioning
confidence: 99%